Demographic and Mental Characteristics of Andijan Region as Factors of Migration - Abdullayev Baxodirjon Maxamadjonovich (American Journal Of Social Sciences And Humanity Research, 2026)
The article provides a socio-philosophical analysis of the demographic and mental characteristics of Andijan region as key factors determining labor migration. The author examines the phenomenon of “social compression” arising from high population density and limited land resources in the region. The study introduces the concept of “Andijan economic ethics” into scholarly discourse, revealing the aspects of labor associated with collective prestige and family responsibility. In addition, based on 2025 statistical data, the article substantiates the destructive forms of migration and the importance of the “close and safe migration” model in preventing them.